2017
DOI: 10.1007/s00068-016-0748-4
|View full text |Cite
|
Sign up to set email alerts
|

Xuebijing injection treatment inhibits vasopermeability and reduces fluid requirements in a canine burn model

Abstract: These results indicate that XBJ injection can reduce fluid requirements by inhibition of neutrophil protease-induced high vasopermeability and tissue edema.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Additionally, He et al (2018) also found XBJ reduced neutrophil counts in BALF and ameliorated lung injury caused by dichlorvos poisoning. XBJ also can reduce the activities of MPO and NE in multiple organ tissues after burn injury ( Tang et al, 2017 ). Chemokines contribute to the neutrophil recruitment, and we further confirmed that XBJ significantly decreased the expressions of inflammatory chemokines including CSF-3, CSF-2, CXCL-3, CXCL-2 and CXCR-2 ( Figure 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, He et al (2018) also found XBJ reduced neutrophil counts in BALF and ameliorated lung injury caused by dichlorvos poisoning. XBJ also can reduce the activities of MPO and NE in multiple organ tissues after burn injury ( Tang et al, 2017 ). Chemokines contribute to the neutrophil recruitment, and we further confirmed that XBJ significantly decreased the expressions of inflammatory chemokines including CSF-3, CSF-2, CXCL-3, CXCL-2 and CXCR-2 ( Figure 3 ).…”
Section: Discussionmentioning
confidence: 99%